Beyond bubbly two-phase flow investigation using a CFD three-field two-fluid model. (April 2019) - Sharma, Subash L.; Ishii, Mamoru; Hibiki, Takashi; Schlegel, Joshua P.; Liu, Yang; Buchanan, John R.
Highlights: Void distribution in a narrow rectangular channel with various non-uniform inlet conditions for beyond bubbly flow conditions. Modeling of void diffusion due to bubble collision phenomena. Validation of the models in an adiabatic air-water two-phase flow. Abstract: Modeling and simulation study of industrial scale beyond-bubbly flows, like cap-bubbly, cap-turbulent and churn-turbulent, using the two-fluid model, has been limited due to the wide range of interfacial length scales involved and lack of physics-based models for bubble hydrodynamics and interaction mechanisms for such flow conditions. One important feature of beyond bubbly flow is the existence of a wide range of bubble sizes and shapes and thus different transport characteristics. The accuracy of two-fluid model predictions is strongly dependent on the constitutive relations used for the two-fluid model. The objectives of this proposed work are the following: select a set of physics-based constitutive relations and implement these models into CFX; evaluate these models for a wide range of test conditions in cap-turbulent and churn-turbulent flows. The interfacial structure is dynamically evaluated using bubble interaction mechanisms (coalescence and break up) from the two-group Interfacial Area Transport Equation implemented as source and sink terms into ANSYS CFX. The assessments for the validity of the models were carried out in comparison to data collected at Purdue University for two-phase flow in a narrow, rectangular duct. Non-uniform inlet conditions were applied in order to evaluate phase diffusion models in CFX. A new turbulence-induced bubble collision diffusion model for the two-group bubbles system has been implemented in ANSYS CFX. The CFD results predict the measured data to within the expected error, correctly capturing the transverse redistribution of phases due to diffusion for both uniform and non-uniform inlet phase distributions. This illustrates the importance of bubble collision phenomena in correctly predicting phase distributions in a channel.